Development of an electromagnetic numerical solver based on the finite difference time domain (FDTD) technique for research and teaching purposes - Ahmad, Nurul 'Atiqah (2015)
A 1D-FDTD code was developed to support plane wave excitation in 3D-FDTD domain and the code was developed using C++ programming language. First-order Mur absorbing boundary condition (ABC) is applied to keep outgoing electric and magnetic fields from being reflected into the problem space. In this thesis, the performance of 1D-FDTD scheme is then evaluated on several medium including free space, lossless dielectric medium, lossy dielectric medium and good conductors. Sine-Gaussian technique is used to excite field signal in the 1D-FDTD simulation domain and the simulation have been carried out to analyze the performance of the scheme. From the results, the 1D-FDTD scheme shows good expected results on all applied conditions. The integration of 1D-FDTD scheme into the 3D-FDTD solver is realized through the implementation of Total Field Scattered Field (TFSF) technique. The technique is used to excite plane wave into the 3D-FDTD domain and will be used for future wave propagation studies. All simulation results presented in this work were analyzed using OriginPro software.